New dalmanitid trilobite taxa from the Lower Devonian of Argentina: Comments on spinosity in endemic taxa from southern high paleolatitudes - Randolfe, Enrique Alberto (2022)
Three new Lower Devonian dalmanitid trilobite taxa are recognized from the Talacasto Formation in the Precordillera Basin, Argentina, which includes two monospecific genera (Ivanites leonorae n. gen., n. sp. and Aguaditaspis mediaspina n. gen., n. sp.), and one additional new genus and species left in open nomenclature. These taxa combine characters of the subfamilies Dalmanitinae Vogdes, 1890 and Synphoriinae Delo, 1935, challenging their taxonomic distinction. Forty percent of the dalmanitids from high paleolatitudinal basins from southwestern Gondwana (Malvinokaffric) exhibit non-homologous dorsal spinosity. Aguaditaspis mediaspina n. gen., n. sp. shares similar spines with Trypaulites calypso (Hall, 1861). The unnamed new genus resembles the spinosity of endemic Malvinokaffric dalmanitids, like Dalmanitoides Delo, 1935 and Fenestraspis Braniša & Vaněk, 1973. Considered defensive, the recorded spinosity along with putative sublethal-attack marks, suggest higher predation pressure than previously thought at high paleolatitudes. This evidence is in accordance with some hypothesis on rising predation pressure in the mid-Paleozoic marine ecosystems.